The way to practice sustainability: wonders of upcycling products - Jasmani, Ismail; Zainal Abidin, Norzalifa (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2019)
Up cycling is a process of converting old or discarded materials into something more useful and creative. It is also gives an item a better purpose. The concept of Up cycling ensures the product is made out of recyclable materials and better than the original product. In another term, up cycling actually increases the value of the product (Thanam Industry, June 2014). Creativity and innovation are the key factors that are needed to produce better and more beautiful products. It is also an easy and simple method which can be followed by others as a way to save our environment. In recent years , though the world of interiors has look into up cycling approach. Instead of being tossed aside and replaced by new furnishings, objects or products are getting re imagined, upgraded and up cycled, giving them a chance to be useful again.( Joanne Lim, 2015). In this chapter, there are seven (7) case study products which were designed and made by the Applied Arts and Design Year 1 students, from the batch 15 session 2018/2019, Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia. The selected works are focusing on different themes : Culture, Nature, Animals, Flowers, Planet and Tree. These themes helped them to express their creativity in choosing the various reusable materials such as plastic bottles, rubber treys, metal motorcycle spare parts, fans, car spring, plastic banners and buntings, tin cans, metal wires etc. the exploration of ideas gave them a sense of maturity in challenging the design creativity by putting the various materials together with colorful tones.